Mahameru Soybean (Glycine max) Cultivar, High Salinity Tolerant - Juwarno Juwarno; Tata Brata Suparjana; Muachiroh Abbas (Biosaintifika: Journal of Biology & Biology Education, 2018)
Mahameru cultivar is high salinity tolerant cultivar. The previous study result showed Mahameru cultivar could tolerate 140mM NaCl, but Cilacap Coast salinity levels often reaching 200mM NaCl. A research of salinity stress on Mahameru cultivar at 200 mM NaCl have not conducted yet. Therefore to conduct the research of Mahameru at high salinity stress to obtained high salinity tolerant soybean cultivar.   The observed variables are anatomy (epidermis thickness, the density of stomata and trichomes, palisade thickness) physiology (the dry weight of roots and canopy, the content of chlorophyll a and b) Production (whole pod, total filled pod, total empty pod, weight per one-hundred beans). The salinity treatment was 0, 50,100, 150, 200 mM NaCl given at three days before planting and twenty-one days after planting. The data of anatomy and physiology was taken at forty-five days after planting. The production data was taken when soybean plants turned brown. The result indicates that salinity affects anatomy characteristic of leaf, higher the salinity increasing epidermis thickness and the density of stomata and trichomes. Salinity affected the content of chlorophyll a and b. Higher the salinity increased the content of chlorophyll a and b. Salinity did not affect soybean production. Based on this study Mahameru cultivar is resistant to salinity up to 200 mM NaCl. The benefit of this research help to enhance national soybean production with utilization coastal land for soybean planting Mahameru cultivar.